Kontroversi Adat Kaharingan dalam Ritual Perkawinan Kristen dan Potensi Moderasi Beragama - Ardi, Ardi; Santoso, Putu Eka Adthiya; Sukmawati, Tuyun; Oktavia, Lilis Sosila; Astawa, I Nyoman Sidi; Tarupay, Heri Kusuma (Satya Dharma : Jurnal Ilmu Hukum, 2025)
The misuse of customary traditions often leads to social conflict. This study examines a specific social conflict arising from the misapplication of sacred Hindu Kaharingan symbols by a Christian couple during their wedding ceremony in Tumbang Batian Village, Murung Raya Regency, Central Kalimantan. This region, particularly Kalimantan, is known for its religious diversity and rich cultural heritage. The findings indicate that the couple's actions caused significant unrest and protest among the Hindu Kaharingan community, who perceived it as a violation of ritual sanctity. This research underscores the importance of religious moderation as a conflict resolution approach. This case highlights existing societal conflicts, and thus, this study aims to address the incident by identifying its triggering factors and exploring resolution methods through the lens of religious moderation. A qualitative approach was employed, utilizing literature reviews and interviews with customary elders and family members. Triangulation techniques were also applied to enhance data validity by comparing findings from various sources and ensuring information consistency. The research results show that the symbols used in Christian traditional wedding rituals are a form of respect from the bride and groom to their ancestors.